Formulasi Dan Uji Stabilitas Sediaan Sabun Mandi Cair Menggunakan Ekstrak Etanol Biji Pala (Myristica Fragrans Houtt) - Djulfikri Mewar; Marisa Anggia Ibrahim; Pikra Parwak (Pusat Riset dan Inovasi Nasional, 2024)
Nutmeg seeds are one of the herbs and spices that are rich in benefits and the content of alkaloids, flavonoids and saponins other very important roles in its utilization. Nutmeg seeds contain trimyristin which its content can be used in the manufacture of liquid bath soap. One of the application of the compound contained is made in the form pHarmaceutical preparations. Liquid soap is made through a saponification reaction from oil and fat reacted with KOH. This research. aim to do optimization of liquid soap formula between concentration variations of 8%, 9%, 10% so can find out the optimum liquid soap formula and know the evaluation of properties pHysics and chemistry of preparations. Nutmeg seed extract is obtained by extraction using the maceration method using 70% ethanol solvent, then carried out evaporation using a rotary evaporator instrument until the extract is obtained thick. Formulation of liquid soap by heating method for 45 minutes. Evaluation preparations include organoleptic observations, homogeneity. pH, foam height. Results showed that the liquid soap formulated from elstract: colored nutmeg brownish, has a characteristic odor of nutmeg seed extract, is in the form of a homogeneous liquid, has a pH pH 8-10, foam height 93mm-139mm. Optimum formula based on results showed no significant difference from all formulas. Variation concentration 8%, 9%, 10% pH test and high foam test. the formula has complied requirements in accordance with the standards set by SNI 06-4085-1996. Where the normal pH of liquid soap is ph 8-11 and the high foam of liquid soap is 13mm-220mm